Discriminative Value of Serum Irisin in Prediction of Heart Failure with Different Phenotypes among Patients with Type 2 Diabetes Mellitus - Berezin, A. A.; Lichtenauer, M.; Boxhammer, E.; Stöhr, E.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2022)
Abstract: Recent studies have shown that circulating levels of irisin are prognostic factors in heart failure (HF), but no data are available on the predictive role of irisin in patients with type 2 diabetes mellitus (T2DM) and different phenotypes of HF. The aim of the study was to investigate whether serum levels of irisin predict HF in T2DM patients. We prospectively included 183 participants with T2DM aged 41 to 62 years (30 non-HF patients and 153 HF patients) and 25 healthy volunteers in the study and evaluated clinical data, hemodynamics and biomarkers (N-terminal pro-brain natriuretic peptide (NT-proBNP) and irisin). Serum levels of irisin < 8.30 ng/mL were found to be a better indicator of HF with reduced ejection fraction (HFrEF) than irisin 8.30 ng/mL, but the predictive cut-off point for NT-proBNP remained the same as for HF with mildly reduced ejection fraction (HFmrEF). Serum levels of irisin < 10.4 ng/mL significantly improved the predictive ability of NTproBNP for HF with preserved ejection fraction (HFpEF). In conclusion, we found that decreased serum levels of irisin significantly predicted HFpEF, rather than HFmrEF and HFrEF, in T2DM patients. This finding may open a new approach to HF risk stratification in T2DM patients.
Berezin A. - https://orcid.org/0000-0002-0446-3999
Keywords: heart failure with preserved ejection fraction; heart failure with mildly reduced ejection fraction; heart failure with reduced ejection fraction; type 2 diabetes mellitus; irisin; natriuretic peptides; prediction